Konsentrasi dan Emisi Gas Karbondioksida (CO2) pada Sedimen Ekosistem Mangrove Desa Nania, Kota Ambon - Dhandi; Tuahatu, Juliana W.; Krisye; Rahman (Coastal and Ocean Journal (COJ), 2024)
Mangrove ecosystem is a type of coastal ecosystem that has many benefits from both ecological, social and economic aspects. The role of mangroves in absorbing carbon reaches 965 tons C/ha. The ability to store carbon is four times more than other ecosystems. Besides absorbing and storing carbon, mangroves also release carbon through litter production. The production of mangrove litter will then experience decomposition resulting in a flux of greenhouse gases. One of the greenhouse gases that triggers climate change is carbon dioxide (CO2). The aim of this research was to determine the concentration and emission values of carbon dioxide (CO2) in the sediments of the mangrove ecosystem of Nania Village, Ambon City. Gas sampling using a syringe through a syringe mounted on a hood. Analysis of gas concentrations used the gas chromatography method. Sediment sampling is carried out using a small shovel on the surface of the substrate under the mangrove canopy. Sediment samples will be analyzed using a sieving process. The results showed that the average concentration of CO2 gas with the highest value in the sandy mud substrate with a value of 701.61 ppm and the lowest in the sand substrate with a value of 561.48 ppm. The largest CO2 gas emission in the mangrove ecosystem sediments of Nania Village was found in the sand sediment type of 75.0535 mg/m2/hour with an emission value, and the lowest was found in mud sediments, namely 30.1899 mg/m2/hour.